A prospective study of health care resource utilisation and selected costs of schizophrenia in France - Sarlon Emmanuelle; Heider Dirk; Millier Aurélie; Azorin Jean-Michel; König Hans-Helmut; Hansen Karina; Angermeyer Matthias C; Aballéa Samuel; Toumi Mondher (BMC, 2012)
Abstract Background Schizophrenia is among the most burdensome and costly illnesses worldwide. To estimate the cost of schizophrenia in France, a longitudinal study was carried out between 1998 and 2002. The main objective of this study was to describe and update the cost of schizophrenia in a longitudinal, representative sample of French patients. The second objective was to identify cost drivers in the treatment of schizophrenia. Methods Based on a cohort of 288 French schizophrenic patients during 2 years of prospective follow-up, this study collected clinical, patient reported outcomes, quality of life, functioning, patient management, care giver involvement and resource utilisation data every 6 months. For each service, information was collected on the type of service, the frequency of attendance and type of intervention provided to the patient. Unit costs were based on available French databases. Mean service use and costs over the five time points were estimated using between-effects regression models. Results In the total sample of 288 patients aged 18-64 years, the mean total cost (€ 3 534) was mainly accounted for by the cost of inpatient treatment (€ 1 390) and day care (€ 1 331). The estimate of the annual cost for direct medical health care for all French schizophrenic patients was € 1 581 million, including € 621 million for inpatient treatment and € 595 million for day care (77%). The costs for medication accounted for 16.1% of total annual costs. The remaining costs (6.9%) included visits to psychiatrists, general practitioners, other physicians and psychologists. The direct resource allocation showed inpatient treatment as the main direct cost. Unemployment was identified as a major indirect cost of schizophrenia treatment. Positive and depressive schizophrenia symptoms at baseline and relapse occurrence during the follow-up period were associated with a higher cost of treatment. Health satisfaction or negative symptoms of schizophrenia at baseline were associated with lower costs. Conclusion Several cost drivers were identified. Based on the results obtained in France, we suggest further analysis of mechanisms that influence the service-specific costs for schizophrenia in other areas of the world.